The great folk discography. Volume 1, Pioneers & early legends - Strong, Martin C. (Polygon, 2010)
The book is divided into American and British-based artists, but it also includes traditional Scottish, Irish, European and Australian performers. The Great Folk Discography ends with an invaluable guide to Cult Collectables - mainly one-LP bands from the 1970s whose recordings command premium prices.
Keywords: Folk music : Discography; folkmusiikki